Enhancing the Organizational Innovation: The Role of HRM Practices and Transformational Leadership in SMEs - Asraf, Asraf; Hakim, Abdul; Yuana, Indira; Roslan, Astil Harli (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objective: The objective of this  research is to reveal the relationship between Human Resource Management (HRM) practices and organizational innovation, mediated by Collective Organizational Engagement and moderated by Transformational Leadership, in the context of small and medium enterprises (SMEs) in Kendari City.Methodology: This study employs a quantitative methodology using Structural Equation Modeling, specifically Partial Least Squares (SEM PLS). The data is cross-sectional, collected at a single point in time through the distribution of questionnaires. The study involves a total of 260 SMEs located in Kendari City.Findings: The study indicates that effective HRM practices foster organizational innovation by creating a supportive work environment. HRM enhances collective employee engagement, contributing to innovation through active participation in idea development. Transformational leadership strengthens this relationship by motivating employees to excel.Conclusion: Efficient HRM practices promote organizational innovation by creating a supportive work environment and enhancing employee engagement. Transformational leadership further accelerates innovation by motivating employees. Integrating effective HRM with transformational leadership creates a conducive environment for sustainable innovation within the organization.